O conhecimento da geodiversidade para o desenvolvimento regional do Cariri Paraibano - Meneses, Leonardo Figueiredo de (2020)
The history of Paraíba's Cariri, Brazil, can fit into a billions-years-long script, marked by powerful events of transformation of its landscape, be it from a structural or from a climatic and biogeographic point of view. Millenial cultural traces are associated to the physical scenery, which can be testified by the rock paintings produced by ancient communities who have long adapted to its hostile climate. The mixture between the colonizers' exotic culture and that of the indigineous people who already inhabited the place, as well as the economic cycles that were established throughout the last centuries, completes the canvas that pictures what Paraíba's Cariri really is: a land of people who fight and resist to the most punishing weather elements, without ever losing the candor in their souls, and whose fallow was settled amidst a sea of flatness, punctuated by rock islands which carry within them some of the history of Planet Earth. Recognizing the beauty which resides in such rocks, in the arid lands, the singular vegetation of Caatinga, and in its people's culture may be a path towards reducing the economic stagnation and showing the world the best that Paraíba's Cariri has to offer. This idea became the objective of this work: to expose the potential use of geodiversity in the counties of Boa Vista, Boqueirão, Cabaceiras and São João do Cariri, aiming at spreading geoscientific knowledge and stimulating new forms of using the territory, in order to distribute, in a more equal manner, the economic and educational benefits that research and tourism activities can offer. Through an inventory, 33 Areas of Geodiversity Interest were identified and described throughout the research process, which were then described in cadastral records. Through the quantification of criteria that represent the expressivity of the geodiversity in these areas, it was then determined those with a level of valuation considered above average in comparison to the universe of studied sites, which resulted in a set of 21 geosites that were considered as parts of the study area's geoheritage. Based on the result of the inventory, suggestions for the use of the local geodiversity were posed, such as the production of geoproducts and ludic activities, and the fomentation for the creation of a geopark, with the creation of a visual identity and of platforms for spreading information on the area's geodiversity, as well as proposing a management structure that can adapt to the area's reality and, finally, the proposal of geotourist itineraries that can include both the current content of the geosites and the cultural attractions of the counties studied in this work. It has also been verified that the technique employed for determining the areas that compose the local geoheritage has proved to be satisfactory, considering that it corroborates with the results obtained in the current registrations of the GEOSSIT system, developed by Serviço Geológico do Brasil/CPRM for Brazil's inventory of geodiversity. The obtained results make it clear that the geodiversity of Paraíba's Cariri is a true patrimony that must be preserved and used in a rational manner as a motor to stimulate the socioeconomic development of its territory.